Factors Influencing the Interest in Using Sharia Digital Banking Applications in Indonesia - Nur Kholidah; Muhammad Arifiyanto; Edy Subowo; Zulfikar Bagus Pambuko (Cakrawala: Jurnal Studi Islam, 2023)
Sharia digital banking represents a recent innovation in the Islamic banking industry. Beyond being a trend, digital banks serve as an adaptation to address emerging changes and threats. The aim of this research is to identify factors influencing interest in using Sharia digital banks. In this case, the author examines the influence of user interface, digital literacy, social factors, brand image, and Sharia financial literacy on the millennial generation's interest in using Sharia digital banking applications in Indonesia. This research involved 100 millennial samples from Pekalongan City. Data analysis employs the Partial Least Square technique. The results reveal that digital literacy, social factors, and brand image significantly and positively influence the millennial generation's interest in using Sharia digital banking applications. Meanwhile, user interface and Islamic financial literacy have a significant negative effect on the millennial generation's interest in using Sharia digital banking applications.